Comparison of effects of two different rehabilitation protocols for acute hamstring strain management in highly-trained athletes - Ghosh, S.; Sharma, J.; Saha, S.; Kushwah, G. S.; Thapa, R. K. (Trends in Sport Sciences, 2025)
Introduction: Hamstring strain injuries (HSIs) are prevalent among athletes and are detrimental to sports performance.